IMPLEMENTATION OF SAK EMKM AS A BASIS FOR FINANCIAL REPORT PREPARATION IN THE TRANSPARENCY AND ACCOUNTABILITY OF MSME FINANCIAL REPORTS FOR PURNAMA LEATHER BAGS IN KLUDAN, TANGGULANGIN, SIDOARJO - Putra, Restu Frandana; Anwar, Chairil; Fahriani, Dian; Wicaksono, Achmad (JEA17: Jurnal Ekonomi Akuntansi, 2025)
The implementation of the Financial Accounting Standards for Micro, Small, and Medium Entities (SAK EMKM) is a strategic step to enhance the transparency and accountability of financial reports for Micro, Small, and Medium Enterprises (MSME) in Indonesia. However, many MSMEs, including Purnama Leather Bags in Kludan, Tanggulangin, Sidoarjo, face challenges in applying these standards due to limited financial literacy and resources. This study aims to analyze the implementation of SAK EMKM in improving financial reporting at Purnama Leather Bags MSME. Using a quantitative descriptive approach, data was collected through structured surveys and financial document analysis. The findings reveal that SAK EMKM implementation enhances financial report quality by providing a structured framework, increasing transparency, and ensuring accountability. However, financial literacy barriers remain a major limitation. The novelty of this study focus on the leathercraft sector, highlighting sector-specific challenges in adopting financial standards. This research implies that increased financial training and digital accounting tools are crucial for ensuring better compliance and sustainability of MSMEs.